The European debt crisis : causes, consequences, measures and remedies - Ari, Ali (Cambridge Scholars Publishing, 2014)
The recent global financial crisis is considered to be the most severe crisis which has led to a synchronised recession since the Great Depression in the 1930s. Europe is the most affected region in the world as a result of this crisis, and, as such, the sovereign debt crisis remains the most important issue in the Eurozone and threatens the future of the EU. This book provides answers, from both theoretical and empirical perspectives, to the following questions: What caused the global and E ...